Synthesis of Novel 1,4-Benzodiazepine-3,5-dione Derivatives: Reaction of 2-Aminobenzamides under Bargellini Reaction Conditions - Mahdavi, Mohammad; Asadi, Mehdi; Saeedi, Mina; Rezaei, Zahra; Moghbel, Hooman; Foroumadi, Alireza; Shafiee, Abbas (Synlett, 2012)
In this paper, we report on a user-friendly synthesis of 1,4-benzodiazepine-3,5-dione derivatives via Bargellini-type reaction. The corresponding products were obtained using various 2-aminobenzamides under Bargellini reaction conditions, in good yields without unfavorable side reaction.
Keywords: Bargellini-type reaction; 1,4-benzodiazepine-3,5-diones; 2-aminobenzamides; heterocycles; dichloro epoxide